2012
DOI: 10.1248/cpb.60.110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-inflammatory Activity of Some Benzofuran and Benzopyran-4-one Derivatives

Abstract: New series of furosalicylic acids 3a-c, furosalicylanilides 6a-n, furobenzoxazines 8a-f, 1-benzofuran-3-arylprop-2-en-1-ones 12a,b, 6-(aryl-3-oxoprop-1-enyl)-4H-chromen-4-ones 16a-c and 6-[6-aryl-2-thioxo-2,5-dihydropyrimidin-4-yl]-4H-chromen-4-ones 17a-c were synthesized. Anti-inflammatory activity evaluation was performed using carrageenan-induced paw edema model in rats and prostaglandin E 2 (PGE 2 ) synthesis inhibition activity. Some of the tested compounds revealed comparable activity with less ulcerogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…It may induce genotoxicity [ 18 ]. Other studies indicate that benzopyran derivatives may be useful anti-inflammatory agents [ 19 ]. Additionally, an antinociceptive effect for 6-isobutyryl-5,7-dimethoxy-2,2-dimethyl-benzopyran was reported in mice mediated by an opioid-like mechanism [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may induce genotoxicity [ 18 ]. Other studies indicate that benzopyran derivatives may be useful anti-inflammatory agents [ 19 ]. Additionally, an antinociceptive effect for 6-isobutyryl-5,7-dimethoxy-2,2-dimethyl-benzopyran was reported in mice mediated by an opioid-like mechanism [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A huge interest on benzofuran-containing compounds has been originated several years ago because of their important biological and pharmacological properties and their extensive natural occurrence [5]. Benzofuran moiety is considered to be an indole isostere (a potent pharmacodynamic moiety exhibiting anti-inflammatory activity) and, consequently, several anti-inflammatory benzofuran-based compounds have been studied [6,7]. However, despite the plethora of reported benzofuran derivatives, 2-arylbenzofurans have not been sufficiently explored at a molecular level for COX-2 inhibition in spite of some of them exhibiting selective in-vitro anti-COX-2 activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent studies showed that novel 1,4,5,6,7,8-hexahydroquinoline derivatives have significant cytotoxic activity against different human cancer cell lines [10][11][12]. Also, literature survey documented that various benzofuran compounds are known to possess important biological properties, including antimicrobial [13][14][15], antifungal [16], antiviral [17], anti-inflammatory [18,19], antidiabetic [20], antioxidant [21,22]. Moreover, many benzofuran derivatives have shown remarkable anticancer activity [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%